PENGARUH PAPARAN DEBU TSP DAN PENGGUNAAN APD TERHADAP GEJALA ISPA PENGGUNA TERMINAL - Iwan Suryadi; Virny Dwiya Lestari; Budirman Budirman; Siti Rachmawati (Politeknik Kesehatan Kemenkes Makassar, 2022)
Symptoms of Acute Respiratory Infection (ARI) are complaints experienced by a person in the respiratory tract. Respiratory tract disease is the third leading cause of death in workers, which is 21%. Some of the causes of ARI are dust exposure and non-compliance with the use of personal protection equipment (PPE), especially those that are in direct contact with dust. This study uses an analytical observational design with a cross sectional approach. Sampling by simple random sampling a number of respondents 80 respondents. Measurement of dust in the work environment using a digital dust monitor, assessment of symptoms of ARI using a questionnaire from the Ministry of Health in 2002 and the use of PPE based on observation sheets. The result of this research is that the average dust concentration is 4.606 mg/m3. for symptoms of ARI the majority of respondents are in the moderate category. The results of the bivariate test showed that there was a significant relationship between dust levels and the use of PPE with ARI symptoms with a p value of 0.045 and 0,024. There is a strong and unidirectional significant relationship between exposure to TSP dust and the use of PPE with ARI symptoms so that terminal users are expected to obey the use of masks to reduce the risk of dust exposure. Keywords : Acute Respiratory Infection, Dust, PPE